Elastic scattering of deuterons by deuterons at Ed ≤ 85 MeV - Beliuskina, O.O.; Grantsev, V.I.; Kisurin, K.K.; Omelchuk, S.E.; Palkin, G.P.; Roznyuk, Yu.S.; Rudenko, B.A.; Semenov, V.S.; Slusarenko, L.I.; Struzhko, B.G. (Вопросы атомной науки и техники, 2011)
The differential cross sections of elastic dd-scattering at Ed = 36.9 MeV in the angular range 30° ≤ Θ c.m. ≤ 116° are measured. For describing of main peak at Θc.m. ≤ 60° we used the diffraction nuclear model taking into account the structure of the colliding nuclei. Satisfactory agreement of the present results with published data at energies of 12.1MeV ≤ Ed ≤ 85 MeV was obtained. For the theoretical interpretation of the angular distributions the identity of the colliding deuterons is taken into account.